Wykorzystanie finansowych instrumentów pochodnych opartych na indeksach HDD/CDD do dywersyfikacji portfela inwestycyjnego - Preś, Juliusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this paper is to demonstrate potentials of weather derivative in asset allocation and portfolio management. The key issues in building portfolio in appropriate way are also discussed. This class of instrument is independent from the other financial markets. The results documented in this article suggest that this factor allows to achieve huge benefits in portfolio diversification. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 166-173